Lobbyism and Climate Change in Fisheries: A Political Support Function Approach - Urs Steiner Brandt (University of Southern Denmark, Department of Environmental and Business Economics (IME), 2005)
This paper seeks to investigate the following issues: What is the resulting out-come, when regulation is determined by interest groups that compete for influ-ence over the regulatory process? Given this, can we predict how climate change related changes in the underlying biological factors will affect the be-haviour of the interest groups and the resulting regulatory outcome.
Keywords: 330; Interessenvertretung; Interessenpolitik; Fischereipolitik; Klimawandel; Neue politische Ökonomie; Politische Willensbildung